Determination of seropositivity for Toxoplasma gondii infection in pregnant and aborted sheep in Elazig and vicinity by Sabin-Feldman (SF) test - Aktas, M; Dumanli, N; Babür, C; Karaer, Z; Öngör, H (Tubitak Scientific & Technological Research Council Turkey, 2000)
This study was conducted in pregnant and aborted sheep to determine Toxoplasma gondii antibodies. Blood samples were collected from a total of 154 sheep from 22 different herds during the period December 1996-January 1997 in Elazig and vicinity. Of these 154 sheep, 56 were pregnant, 57 aborted in the previous year and the remaining 41 sheep aborted within the period of the study. Sera obtained properly from these blood samples were examined by Sabine-Feldman (SF) test. Seropositivity for Toxoplasma gondii infection was determined in 72 (46.8%) of the 154 sheep at the titers ranging from 1/16 to 1/1024. The seropositivity rates of 48.2%, 45.6% and 46.3% were obtained in pregnant sheep, sheep which had aborted in the previous year and sheep which aborted within the study period, respectively.
Keywords: Toxoplasma gondii; sheep; SF